"I think gorilla-like back effusions of hair are rather a turn-off": 'Excessive hair' and male body hair (removal) discourse. (June 2016) - Terry, Gareth; Braun, Virginia
Highlights: Thematic analysis generated three themes 'explaining' men's hair removal. Two contradictory themes: men's hair as natural, men's hair as unpleasant. A third theme: Groom 'excess' hair provides interpretative framework. Men's body hair practices associated with changes in masculinities. Vagueness of notion of excess may provoke anxiety and body hair removal. Abstract: Men's hair removal practices are becoming mainstream, seen as a consequence of changing masculine norms and men's relationships to their bodies. This is often presented as a straightforward 'shift' from men's ideal bodies as naturally hairy, to increased hairlessness, and the consequence on men's body concerns as inevitable. This paper analyses qualitative survey data from Aotearoa/New Zealand using critical thematic analysis, and describes three themes. Two themes capture contradictory ideas: that men's body hair is natural, and that men's body hair is unpleasant. A third theme introduces the concept of 'excess' hair, which allowed sense-making of this contradiction, mandating men's grooming of 'excessive' hair. However its vagueness as a concept may provoke anxiety for men resulting in hair removal. This paper adds to a body of research demonstrating a cultural transition: the ways changing masculinities, increased commodification of male bodies, and shifting gender roles impact on men's hair removal practices.